Comparative study of the complete mitochondrial genomes of the bronze gudgeon (Coreius heterodon) and largemouth bronze gudgeon (Coreius guichenoti). (June 2013) - Xu, Dandan; Li, Ping; Zhang, Yaoguang; Peng, Zuogang
<x xml:space="preserve">Abstract</x> The bronze gudgeon (Coreius heterodon) and the congeneric species largemouth bronze gudgeon (Coreius guichenoti), two endemic fish species in China, are important economic fishes in local areas. The bronze gudgeon is distributed in Yangtze River and Huanghe River basin, whereas the largemouth bronze gudgeon is distributed only in the middle and upper reaches of Yangtze River. Here, we sequenced the complete mitochondrial genomes of the two species and compared the evolutionary rate differences between the two species. The complete mitochondrial genomes of C. heterodon and C. guichenoti are 16, 611 and 16, 612 bp, respectively. Both of the complete mitogenome sequences contain 13 protein-coding genes, 2 rRNA subunits, 22 tRNAs and 1 non-coding control region, which are typical vertebrate mitogenomes. The relative rate test shows that the mitochondrial genome of C. heterodon evolves nearly threefold faster than that of C. guichenoti, which is mostly caused by the higher substitution rates in rRNAs and especially in tRNAs in C. heterodon.